2022
DOI: 10.1021/acs.est.2c01774
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Regulated Release of Distinctive Volatile Organic Compounds from Stressed Living Cells

Abstract: Breath-borne volatile organic compounds (VOCs) have been increasingly studied as non-invasive biomarkers in both medical diagnosis and environmental health research. Recently, changes in breath-borne VOC fingerprints were demonstrated in rats and humans following pollutant exposures. In this study, the eukaryotic model Saccharomyces cerevisiae was used to study the release of cellular VOCs resulting from toxicant exposures (i.e., O3, H2O2, and CO2) and its underlying biological mechanism. Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Several studies have reported the detection of various aldehydes, such as acetaldehyde, heptanal, hexanal, nonanal, and octanal, in the exhaled breath of patients with various diseases, suggesting their potential as biomarkers for disease diagnosis. 20,23,49,50 Our findings indicate a persistent increase in pentanal, hexanal-M, hexanal-D, heptanal-M, and (E)-2-hexenal in the exhaled VOCs of rats exposed to PMSF for 6 days. This observation suggests that the body may have undergone pathological changes, potentially linked to the incomplete degradation of fatty acids.…”
Section: Changes In Nontargeted Serum Metabolites Of Rats After Expos...mentioning
confidence: 53%
See 3 more Smart Citations
“…Several studies have reported the detection of various aldehydes, such as acetaldehyde, heptanal, hexanal, nonanal, and octanal, in the exhaled breath of patients with various diseases, suggesting their potential as biomarkers for disease diagnosis. 20,23,49,50 Our findings indicate a persistent increase in pentanal, hexanal-M, hexanal-D, heptanal-M, and (E)-2-hexenal in the exhaled VOCs of rats exposed to PMSF for 6 days. This observation suggests that the body may have undergone pathological changes, potentially linked to the incomplete degradation of fatty acids.…”
Section: Changes In Nontargeted Serum Metabolites Of Rats After Expos...mentioning
confidence: 53%
“…Molecular Mechanism behind Exhaled VOC Profiles of Rats. Through literature research and the KEGG pathway analysis, 23,28,29,43,44 we identified the molecular mechanisms behind 13 biomarkers of exhaled VOCs (Figure 5). We found that the citrate cycle (TCA cycle), the fundamental metabolic pathway for the breakdown of carbohydrates, fats, and proteins in cell mitochondria, 45,46 is closely related to the production of ketones (hydroxyacetone and acetone), acids (acetic acid and lactate), and alcohols (1-propanol and butan-1-ol) in exhaled VOCs.…”
Section: Changes In Nontargeted Serum Metabolites Of Rats After Expos...mentioning
confidence: 99%
See 2 more Smart Citations